Modern Athletes’ Preparation for the Olympic Games - Karoblis, Povilas; Balčiūnas, Egidijus; Petkus, Einius; Tamulevičius, Robertas (Pedagogika, 2015)
Sport training process has its own problems related to different sport disciplines, thus, it is essential effectively to employ sport scientists’ and coaches’ initiatives as well as their researches and gained experience. The most important sport science function is to accept and share new technologies and good practices through sport training theory and didactics alongside to the new challenges for high performance sport that settle new requirements for coaches’ competency. Such tendencies are already reflected in present scientific studies and training modes of high performance athletes. Coaching more and more appears to come as many-angled process for athletes, who strive for elite level and must be prepared to stay at this level for many years ahead; and this involves not only coach’s specific, profession-related, and general competencies but also other parties-scientists, medics, managers-alongside to national support. When planning athletes’ training process for the Olympic Games, it is necessary to take into consideration the tendencies of sport and event perspectives as well as tendencies to anticipate results. The data of athlete’s main characteristics analysis, changes in sport training methods and its strategy, the development of increasing training loads, material facilities and technical equipment must be considered too. After analysing this, the training and participation in competitions of athletes and other participants has to be acquainted and summarized; then coach’s insights that are prognostic for sport results can be welcomed. Eventually, qualitative criteria for training evaluation must be settled, considering its scientific relevance, originality, influence to new scientific researches as well as scientists’ public behaviour, tolerance, and proper area-related growth stimulation.